2013
DOI: 10.5812/ircmj.3804
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Colonic J-pouch and Straight Coloanal anastomosis after Low Anterior Resection

Abstract: BackgroundThe tendency towards sphincter preserving for low rectal cancers with low anterior resection, has led to the technique of straight coloanal anastomosis (SCAA) or colonic J-pouch anal anastomosis (CPAA).ObjectivesThe aim of our study was to compare functional outcomes, complication rates and quality of life (QoL) after LAR with either a straight or colonic J pouch anastomosis.Patients and MethodsIn 88 patients with rectal tumors located in lower third, who were candidate for LAR with coloanal anastomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Some studies have found that the main causes of DD may be anatomical damage, 7 8 nerve damage, 9 10 sphincter damage, 11 rectal dynamic change 12 13 and Open access the effects of preoperative chemoradiotherapy. 14 15 DD is most evident in the initial period after surgery and will continue for 1-2 years. Worse still, this series of defecation disorder syndromes might accompany patients through their life, and bring about harm to their daily life and social activities.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that the main causes of DD may be anatomical damage, 7 8 nerve damage, 9 10 sphincter damage, 11 rectal dynamic change 12 13 and Open access the effects of preoperative chemoradiotherapy. 14 15 DD is most evident in the initial period after surgery and will continue for 1-2 years. Worse still, this series of defecation disorder syndromes might accompany patients through their life, and bring about harm to their daily life and social activities.…”
Section: Introductionmentioning
confidence: 99%